IMPLEMENTASI PERANGKAT PELATIHAN HIGIENE SANITASI UNTUK MENINGKATKAN KEMAMPUAN PENJAMAH MAKANAN â€œPIA IBU SLAMETâ€ DI TUGU KEPATIHAN KOTA JOMBANG - Mustaqimah, Thoriqotul (Jurnal Tata Boga, 2018)
Abstract This research was aimed to find out: 1) implementation of sanitation training for food handler hygiene, 2) activity of sanitation training of food handler hygiene, 3) result of sanitation test of food handler sanitation hygiene, 4) response of sanitation trainee of sanitation of food handler. This research is a pre-experiment research with pretest and post-test group design. The data obtained are the result of training implementation, the activity of the trainee, the pre-test and post-test result of improvement of food handler